The Mass Change Designated Observable Study: Overview and Results. Issue 8 (8th August 2022) - Wiese, D. N.; Bienstock, B.; Blackwood, C.; Chrone, J.; Loomis, B. D.; Sauber, J.; Rodell, M.; Baize, R.; Bearden, D.; Case, K.; Horner, S.; Luthcke, S.; et al.
Abstract: The 2017–2027 United States National Academy of Sciences Decadal Survey (DS) for Earth Science and Applications from Space identified Mass Change (MC) as one of five Designated Observables (DOs) having the highest priority in terms of Earth observations required to advance Earth system science over the next decade. In response to this designation, NASA initiated several multi‐center studies, with the goal of recommending observing system architectures for each DO for implementation within this decade. This paper provides an overview of the Mass Change Designated Observable (MCDO) Study along with key findings. The study process included: (a) generation of a Science and Applications Traceability Matrix (SATM) that maps required measurement parameters to the DS Science and Applications Objectives; (b) identification of three architecture classes relevant for measuring mass change: Precise Orbit Determination (POD), Satellite‐Satellite‐Tracking (SST) and Gravity Gradiometry (GG), along with variants within each architecture class; and (c) creation of a Value Framework process that considers science value, cost, risk, schedule, and partnership opportunities, to identify and recommend high value observing systems for further in‐depth study. The study team recommended the implementation of an SST architecture, and identified variants that simultaneously (a) satisfy the baseline measurement parameters of the SATM; (b) maximize the probability of providing overlap with the Gravity Recovery and Climate Experiment Follow‐On (GRACE‐FO) mission currently in operation, accelerating science return from both missions; and (c) provide a pathway towards substantial improvements in resolution and accuracy of mass change data products relative to the program of record. Plain Language Summary: This study provides an overview of the Mass Change Designated Observable Study. The goals of the study were to recommend observing systems for NASA to implement within this decade to measure Earth system mass change, after it was identified in the United States National Academy of Sciences Decadal Survey as one of the five most important observations to advance Earth system science. Mass change observations are critical to understanding changes in sea level, the health of the ice sheets and glaciers worldwide, and changes in freshwater availability across the globe. The study team recommended that NASA implement an architecture similar in nature to its two predecessor missions: the Gravity Recovery and Climate Experiment (GRACE), and GRACE Follow‐On (GRACE‐FO). This will maximize the chances that there will not be a data gap between GRACE‐FO (currently operational) and the next observing system. Further, the study team recommended collaborating with potential international partners to add more satellites to this architecture, in order to improve resolution of Earth system mass change in space and time. Key Points: A Science and Applications Traceability Matrix to satisfy the 2017 Earth Science Decadal Survey Mass Change Science Objectives was developed A value framework process was used to identify and evaluate high‐value mass change observing systems for implementation within this decade High value observing systems provide continuity with Gravity Recovery and Climate Experiment Follow‐On and a pathway for improved resolution and accuracy in resolving mass change